Activate Your Health, a 3-year, multi-site, workplace healthy lifestyle promotion program: study design - Thiffya Arabi Kugathasan; François Lecot; Suzanne Laberge; Jonathan Tremblay; Marie-Eve Mathieu (BMC, 2019)
Abstract Background Workplace Health Promotion Programs (WHPP) have been shown to be an efficient way of improving workers' health. These programs can be incorporated in the worker's daily schedule and improve their productivity at work. Improving employees' health also benefits the employers by increasing their return on investment and lowering healthcare costs. The Activate Your Health program, created by Capsana in 2015, is a WHPP targeting multiple lifestyle habits for a three-year period. This WHPP includes tailored web-based interventions and the support of different health professionals throughout the years. We hypothesize that this approach will yield long-term lifestyle changes. The objective of the current paper is to describe the Activate Your Health program's design. Methods/design Eleven companies are taking part in this WHPP and had to choose among five different options of this program and all their employees were encouraged to participate. Each option differs by the number and type of interventions included. The limited option, which is considered the control group, only consists in completing a questionnaire regarding their health status, lifestyle habits and behaviors. On the other end, the extensive option receives a combination of multiple interventions: online menus, health challenges, support in creating a healthy work environment, coaching by health professionals (nurse, nutritionist, and kinesiologist), health screening and flexibility assessment, online resources, social health platform, and activity tracking. The remaining options are in between these options and vary by the amount of intervention. Baseline data are already gathered; two other data collection periods will take place after one and 2 years into the program. The primary outcomes of the current program are physical activity and fitness measures, nutritional data, smoking habits, stress and intention to change. Discussion The Activate Your Health program will allow us to compare which combinations of interventions are the most effective. It is expected that the extensive option will be the most advantageous to improve lifestyle habits. The results will indicate the strength and weakness of each intervention and how it could be improved. Trial registration Clinicaltrails.gov, registration number: NCT02933385 (updated on the 26th of March 2019, initially registered on the 5th of October 2016).